Analysis Of Bosnia-Herzegovina Armed Conflict - Ridha Ayu Rachmawati; Herlina Juni Risma Saragih; I Gede Sumertha Kusuma Yanca; Pujo Widodo (CV. AFDIFAL MAJU BERKAH, 2023)
The Bosnia-Herzegovina conflict in 1992 was a war that had its roots in the ethnic conflict (1992–1995) in Bosnia and Herzegovina, a former Yugoslav Republic with a multiethnic population consisting of Bosniaks (Bosnian Muslims), Serbs, and Croats. The Bosnia-Herzegovina conflict was a Non-International Armed Conflict (NIAC) which turned into an International Armed Conflict (NIAC). Factors causing conflict include ethnic and religious differences, the death of President Josip Broz Tito, the political policies of President Slobodan Milosevic, strategic areas, competition for natural and industrial resources, recognition of independence by the European Community and international organizations, and the economic crisis. International organizations that participated in ending the Bosnia-Herzegovina conflict include the UN, UNPROFOR, NATO, IFOR, SFOR, NAC, SHAPE, COMARCC, OIC, and NAM. After years of fierce fighting involving the three groups, Western countries, with the support of NATO, implemented a final ceasefire negotiated in Dayton, Ohio, USA, in 1995. This research uses qualitative research methods. Data presentation is carried out descriptively based on a comprehensive literature study from books, journals, and news to examine an event that has occurred objectively using existing theoretical approaches.